2018
DOI: 10.2146/ajhp170682
|View full text |Cite
|
Sign up to set email alerts
|

Entry-level practice requirements of pharmacy technicians across the United States: A review

Abstract: There is no consensus among the 50 states and the District of Columbia regarding entry-level requirements for pharmacy technicians, which range from no oversight to mandatory training/education with or without certification requirements. Several national organizations have set recommendations for minimal education/training and certification; however, there is no uniform acceptance across the United States.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Given their role in the dispensing process, inventory management, and other aspects of the pharmacy, technicians play a vital role in fostering an environment that promotes safe and effective medication use. For example, Odukoya, Schleiden, and Chui (2015), found that pharmacy technicians play a vital role in preventing e-prescribing errors by catching errors before the prescription is sent to the pharmacist to verify [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given their role in the dispensing process, inventory management, and other aspects of the pharmacy, technicians play a vital role in fostering an environment that promotes safe and effective medication use. For example, Odukoya, Schleiden, and Chui (2015), found that pharmacy technicians play a vital role in preventing e-prescribing errors by catching errors before the prescription is sent to the pharmacist to verify [16].…”
Section: Discussionmentioning
confidence: 99%
“…While only 16 states required any training programs for entry-level pharmacy technicians. This study reveals the legal requirements for the employment of pharmacy technicians, but did not study or discuss what employers actually look for in pharmacy technician candidates [16]. Therefore, the overall objective of this study was to look at the pharmacy technician advertisement database from the Pharmacy Week to find patterns and commonalities in the duties and qualifications of pharmacy technicians.…”
Section: Introductionmentioning
confidence: 99%
“… 9 12 Each member state has its own regulations including definition of pharmacy technician, varying minimum entry requirements from no formalised training or certification to graduation from an accredited training programme and national certification. 13 Two categories exist, that is, entry and advanced pharmacy technician level with clearly defined roles and responsibilities. 3 Career pathing includes being a pharmacy technician, senior or lead technician with limited opportunity for management positions although some are performing leadership functions.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, uniform prerequisites for the employment of pharmacy technicians are currently nonexistent. 5,6…”
Section: Introductionmentioning
confidence: 99%